Assessment of the Performance of Three Multiplex Array Panels for the Detection of Circulating Cytokines and Chemokines in Naive, LPS, and SEB-treated Cynomolgus Macaques. (January 2014) - He, Ching; Narayanan, Padma K.; Fort, Madeline M.
To assess relative sensitivity for detection of cytokines and chemokines in cynomolgus serum samples, we tested three commercially available multiplex array kits using the Luminex® platform with sera from animals exposed by intravenous injection to 150 μg/kg staphylococcal enterotoxin B (SEB) or 20 μg/kg lipopolysaccharide (LPS). Each of these kits detected similar patterns of changes in circulating cytokines/chemokines in response to SEB or LPS stimulation, especially the induction of high amounts of interleukin (IL)-2 and interferon-gamma (IFN-γ) in response to SEB but not LPS. However, there were clear differences in sensitivity for particular analytes, especially for IL-10. Additional experiments that focused on one multiplex array kit demonstrated very low or undetectable levels of cytokines in naive cynomolgus macaques, except for highly variable background levels of IL-8, monocyte chemoattractant protein-1, and macrophage inflammatory protein-1β. Therefore, multiplex array analysis of circulating cytokine/chemokine patterns was capable of detection of systemic activation of diverse immune cell subsets.